Effect of necrotrophic fungus and PGPR on the comparative histochemistry of Vigna radiata by using multiple microscopic techniques. Issue 11 (24th May 2021) - Javed, Sidra; Javaid, Arshad; Hanif, Uzma; Bahadur, Saraj; Sultana, Shazia; Shuaib, Muhammad; Ali, Sajjad
Abstract: Rapid advances in the field of pathogen detection have opened new opportunities and better understanding for their management approaches. Aim of this study was to elucidate histopathological observations of different tissues affected by Macrophomina phaseolina and to observe the defense responses of plant growth promoting rhizobacteria (PGPR) in mungbean plants. Sections of the stem and root were prepared and stained with ferric chloride, Lugol's iodine and Wiesner's reagent and were then observed under multiple microscopic techniques. Results revealed that both pathogen and PGPR produce responses on the plant that include colonization of xylem vessels by hyphae and sclerotia, hypertrophy and hyperplasia of the cells, destruction of xylem fibers and amyloplasts in parenchymatous cells; and production of gels by the plant were observed. There was a significant increase in lignin and phenolic compounds deposition in stem and root sections of PGPR treated and non‐treated mungbean plants. Whereas the soil amended with PGPR showed very less to no starch production. Moreover, production of gels and gums were also observed in both stem and root sections. Compared to light microscopy, scanning electron microscope provided greater depth of focus and resolution of the pathogen attack on plant tissues, associated bacteria. As a whole, the data demonstrated that inoculation of PGPR can be an effective strategy to stimulate plant growth and they could significantly activate disease resistance against M. phaseolina . Abstract : Plant growth promoting rhizobacteria (PGPR) are the rhizospheric bacteria that may be used to enhance plant growth and repress plant diseases. Macrophomina phaseolina is a necrotrophic fungal pathogen that causes charcoal rot disease in mungbean. Increase in deposition of lignin, phenolic complexes in root and stem segments of plants treated with PGPR were observed by using the advance protocol of light and scanning electron microscopy. PGPR can effectively stimulate plant growth and could significantly activate disease resistance against M. phaseolina .